DIFFERENTIAL DIAGNOSIS OF MYOCARDIAL DAMAGE IN REVERSIBLE DILATION OF THE CARDIAC CHAMBERS - G. E. Roitberg; I. D. Slastnikova; L. K. Merzyavko (Klinicist)
The paper describes a case of a 46-year-old patient who has applied as having heart failure signs in the presence of enlarged cardiac chambers.A follow-up shows a favorable outcome with complete normalization of cardiac chamber sizes. Laboratory and instrumental findings (electrocardiograms, chest X-ray films, echocardiograms) are given. The possible reversible causes of dilated cardiomyopathy are discussed.